What point in the feasibility region maximizes the objective function?Objective Function: C = 5x - 4y
What point in the feasibility region maximizes the objective function? - 1

Answers

Answer 1
Answer:

In general, you solve a problem like this by identifying the vertices of the feasible region. Graphing is often a good way to do it, or you can solve the equations pairwise to identify the x- and y-values that are at the limits of the region.

In the attached graph, the solution spaces of the last two constraints are shown in red and blue, and their overlap is shown in purple. Hence the vertices of the feasible region are the vertices of the purple area: (0, 0), (0, 1), (1.5, 1.5), and (3, 0).

The signs of the variables in the contraint function (+ for x, - for y) tell you that to maximize C, you want to make y as small as possible, while making x as large as possible at the same time. The solution space vertex that does that is (3, 0).

Answer 2
Answer:

To solve a problem like this, we can identify the vertices of the feasible region.

The vertex that satisfies this is (3, 0). Therefore, the maximum value of C is 3.

What is the Feasible Region?

The feasible region is the area where all the constraints are satisfied. In this case, the feasible region is the purple area in the graph. The vertices of the feasible region are (0, 0), (0, 1), (1.5, 1.5), and (3, 0).

To maximize C, we want to make y as small as possible and x as large as possible. The vertex that satisfies this is (3, 0). Therefore, the maximum value of C is 3.

Read more about vertex here:

brainly.com/question/21191648

#SPJ4


Related Questions

Elisha is a photographer and charges a set fee to photograph weddings. This is an example of _____ income.a. capital gains b. earned c. hourly d. passive
What is the measure of the indicated angle 103° ?
(4u^3+6u^2+7)+(6u^3-2u+7) Simplify the sum'
Andy is scuba diving.He starts at sea level and then descends 10 feet in 2 1/2 minutes. a. how would you represent Andy's descend as a unit rate? Express your answer as an integer. b. How much feet can he descend in 6 minutes?
Need help solving thisA. 13B. 9.8C. 19D. 8.7

Rewrite f(x) = –2(x − 3)2 + 2 from vertex form to standard form. pleae help.

Answers

f(x) = -2(x - 3)² + 2
f(x) = -2(x - 3)(x - 3) + 2
f(x) = -2[x(x - 3) - 3(x - 3)] + 2
f(x) = -2[x(x) - x(3) - 3(x) - 3(-3)] + 2
f(x) = -2(x² - 3x - 3x + 9) + 2
f(x) = -2(x² - 6x + 9) + 2
f(x) = -2(x²) - 2(-6x) - 2(9) + 2
f(x) = -2x² + 12x - 18 + 2
f(x) = -2x² + 12x - 16
f(x)=-2(x-3)2+2=f(x)=-2(x-3)

Why might you want to use thecommutative property to change the order of the integers in the following sum before adding?

Answers

Answer :

You can use commutative property or can not be .It is not necessary to use it for given addition of integers.

Step-by-step explanation:

We are given that an expression

-80+(-173)+(-20)

By simplfy simply without using commutative property

-80-173-20=-273

Because minus minus is plus then all integers will be added.

Simplfy by using commutative property

-80+(-173)+(-20)

-80+(-20)+(-173)  (Commutative property a+b=b+a)

-100+(-173)=-273

The answer should not change .Hence, if you want use commutative property to change the order of the integers then answer does not effected.So, you can use it or can not be .

u would do this because no matter the order, the answer will be the same

Your bowling ball weighs 1414 pounds. How much does it weigh in ounces?

Answers

1 pound equals to 16 ounces then 16 multiply by 1414 answer is 22624

How many times does 4 go into 85?

Answers

85 divided by 4 equals to 21 and one-fourth.
hope it helped!
hit the brainiest button pleaseee!

4^3 • 5^3 and 20^3, Are the expressions equivalent? Yes or no?

Answers

Hey there!

4^3 * 5^3 = ?

4^3

= 4 * 4 * 4

= 16 * 4

= [64]

5^3

= 5 * 5 * 5

= 25 * 5

= [125]

125 * 64

= [8,000]

20^3

= 20 * 20 * 20

= 400 * 20

= 8,000

8,000 = [8,000]

Therefore, this statement is TRUE so your answer is: [YES]

Good luck on your assignment and enjoy your day!

~Amphitrite1040:)

Answer:

Yes

Step-by-step explanation:

4³ × 5³

(4 × 5)³

=20³

Both are equivalent

For questions 1-7, use the following functions to answer the questions: f(x)x^2+5x g(x)=3x-4/2

Answers

Answer:

f(4) = (4)² + 5(4) = 36.

g(9) = [3(9) - 4]/2 = 23/2.

f(-3) = (-3)² + 5(-3) = -6.

g(-6) = [3(-6) - 4]/2 = -11.

Set f(x) = 14.

=> x² + 5x = 14

=> x² + 5x - 14 = 0

=> (x + 7)(x - 2) = 0

=> x = -7 or x = 2.

Set g(x) = -28.

=> (3x - 4)/2 = -28

=> 3x - 4 = -56

=> 3x = -52

=> x = -52/3.

Answer:

36

11.5

6

-11

-2, 7

-17.333 / - 17⅓

Step-by-step explanation:

f(4) = 4² + 5(4) = 16+20 = 36

g(9) = 3(9)-4 ÷ 2 = 23÷2 = 11.5

f(-3) = (-3)²+5(-3) = 9 - 15 = 6

g(-6) = 3(-6)-4 ÷ 2 = - 22 ÷ 2 = - 11

f(x) = 14

x² - 5x = 14

x² - 5x - 14 = 0

(x+2) (x-7) = 0

x = - 2 or x = 7

g(x) = -28

(3x - 4)/(2) = - 28

3x - 4 = - 56

3x = - 52

x = - 52/3 = - 17 ⅓